Over-generalization, Under-generalization, and No-generalization on a Child’s Language Acquisition - Akhmad Baihaqi (Journal of English Language Studies, 2020)
It seems that many young children may not comprehend the word-reference relationship even though they can produce the words accurately. Since it happens, the children may face the situation known as over-generalization, under-generalization, and no-generalization. This study aims to get an in-depth understanding of over-generalization, under-generalization, and no-generalization on a child’s language acquisition. The method of research was a case study. The subject of research was a two-year-old child. Data of research were collected from the result of participant observation and documentation of speech transcription. Data analysis of this research covered data reduction, data display, and conclusion drawing or verification. The result shows that (1) over-generalization, under-generalization, and no-generalization occur when the subject aged 26 to 30 months; (2) at aged 32 months, those errors are finally revealed since the subject can manage his cognitive development and conceptualize his semantic-reference relationship for particular properties; and (3) this also proves that environment has a massive role to support and stimulate a child in acquiring and producing his language